Alteração do nome e do sexo civil da pessoa transgênero como concretização do direito à identidade - Marinho, Neumalyna Lacerda Alves Dantas (2017)
The present research is about the change of the name and sex of the transgender people in the civil registry as concretion instrument of the right to identity, with the general aim of discussing the need to change the name and gender in the civil identification documents of the transgender individuals to fulfill this fundamental right. The name is an important means of identification and social individualization of the subject and is tied to the fundamental right to identity, fails to fulfill its social function at the moment it denies identification individually and before the society of the individual. Transgender people routinely suffer from the process of exclusion, discrimination and stigma because they do not fit the norms imposed by cisnormative society, experiencing a non-effectiveness in their fundamental human rights such as work, health and education and the non-recognition of the right to identity interferes too much in this process. Currently, the change in the pre-order and civil sex of the transsexual individuals is mostly linked to the submission of transgenital surgery. The first section of this research deals with the main aspects of transsexual people, the second chapter highlights human rights and the ineffectiveness of these individuals' fundamental rights, and the third, the general aspects about the right to personal identity as a fundamental right of transsexuals, discussing possibility of mutability of the name, the decisions of some country courts to grant a name change and civil sex limited to transgender surgery, and the non-realization of the right to identity, since other means exist that guarantee legal certainty in social relations, besides biological sex. Therefore, the present dissertation accompanies exploratory research, the scientific method used is the deductive, the bibliographical and documental research of existing productions is used, besides other legal texts and jurisprudential that deal with the matter.